Non-HLA Antibodies and Epitope Mismatches in Kidney Transplant Recipients With Histological Antibody-Mediated Rejection - Crespo, Marta; Llinàs-Mallol, Laura; Redondo-Pachón, Dolores; Butler, Carrie; Gimeno, Javier; Pérez-Sáez, María José; Burballa, Carla; Buxeda, Anna; Arias-Cabrales, Carlos; Folgueiras, Montserrat; Sanz-Ureña, Sara; Valenzuela, Nicole M.; et al. (Frontiers in Immunology, 2021)
Background Correlation between antibody-mediated rejection (ABMR) and circulating HLA donor-specific antibodies (HLA-DSA) is strong but imperfect in kidney transplant (KT) recipients, raising the possibility of undetected HLA-DSA or non-HLA antibodies contributing to ABMR. Detailed evaluation of the degree of HLA matching together with the identification of non-HLA antibodies in KT may help to decipher the antibody involved. Methods We retrospectively assessed patients with transplant biopsies scored following Banff’15 classification. Pre- and post-transplant serum samples were checked for HLA and non-HLA antibodies [MICA-Ab, angiotensin-II type-1-receptor (AT1R)-Ab, endothelin-1 type-A-receptor (ETAR)-Ab and crossmatches with primary aortic endothelial cells (EC-XM)]. We also analyzed HLA epitope mismatches (HLA-EM) between donors and recipients to explore their role in ABMR histology (ABMRh) with and without HLA-DSA. Results One-hundred eighteen patients with normal histology (n = 19), ABMRh (n = 52) or IFTA (n = 47) were studied. ABMRh patients were HLA-DSApos (n = 38, 73%) or HLA-DSAneg (n = 14, 27%). Pre-transplant HLA-DSA and AT1R-Ab were more frequent in ABMRh compared with IFTA and normal histology cases (p = 0.006 and 0.003), without differences in other non-HLA antibodies. Only three ABMRhDSAneg cases showed non-HLA antibodies. ABMRhDSAneg and ABMRhDSApos cases showed similar biopsy changes and graft-survival. Both total class II and DRB1 HLA-EM were associated with ABMRhDSApos but not with ABMRhDSAneg. Multivariate analysis showed that pre-transplant HLA-DSA (OR: 3.69 [1.31–10.37], p = 0.013) and AT1R-Ab (OR: 5.47 [1.78–16.76], p = 0.003) were independent predictors of ABMRhDSApos. Conclusions In conclusion, pre-transplant AT1R-Ab is frequently found in ABMRhDSApos patients. However, AT1R-Ab, MICA-Ab, ETAR-Ab or EC-XM+ are rarely found among ABMRhDSAneg patients. Pre-transplant AT1R-Ab may act synergistically with preformed or de novo HLA-DSA to produce ABMRhDSApos but not ABMRhDSAneg. HLA epitope mismatch associates with ABMRhDSApos compared with ABMRhDSAneg, suggesting factors other than HLA are responsible for the damage.